Engineering antiviral immune-like systems for autonomous virus detection and inhibition in mice - Wang, Yidan; Xu, Ying; Tan, Chee Wah; Qiao, Longliang; Chia, Wan Ni; Zhang, Hongyi; Huang, Qin; Deng, Zhenqiang; Wang, Ziwei; Wang, Xi; Shen, Xurui; Liu, Canyu; et al. (Nature communications, 2022)
The ongoing COVID-19 pandemic has demonstrated that viral diseases represent an enormous public health and economic threat to mankind and that individuals with compromised immune systems are at greater risk of complications and death from viral diseases. The development of broad-spectrum antivirals is an important part of pandemic preparedness. Here, we have engineer a series of designer cells which we term a utonomous, intel li gent, virus-indu c ible immune-lik e (ALICE) cells as sense-and-destroy antiviral system. After developing a destabilized STING-based sensor to detect viruses from seven different genera, we have used a synthetic signal transduction system to link viral detection to the expression of multiple antiviral effector molecules, including antiviral cytokines, a CRISPR-Cas9 module for viral degradation and the secretion of a neutralizing antibody. We perform a proof-of-concept study using multiple iterations of our ALICE system in vitro, followed by in vivo functionality testing in mice. We show that dual output ALICE SaCas9+Ab system delivered by an AAV-vector inhibited viral infection in herpetic simplex keratitis (HSK) mouse model. Our work demonstrates that viral detection and antiviral countermeasures can be paired for intelligent sense-and-destroy applications as a flexible and innovative method against virus infection. The development of broad-spectrum antivirals is an important part of pandemic preparedness and response. Here the authors present ALICE, synthetic biology designer immune-like cells that act as a sense-and-destroy antiviral system can detect viruses from seven different genera, mimicking the human innate immune system.